PENGELOLAAN DAN PENYALURAN DANA DESA (BUMDES) BERBASIS SYARIAH DI DESA TANAK AWU PUJUT - Ahadiah Agustina; Nurul Huda (Jurnal Ilmiah Ekonomi Islam, 2022)
One of the allocations of village funds is for village economic development. BUMDes is one of the economic institutions established and managed by the village government which aims to empower and develop the village economy. The development of Islamic economics or commonly known as Islamic economics in Indonesia is taking place so rapidly. The application of Islamic economics is currently still developing in the financial sector. This study aims to design the management and distribution of village funds based on sharia principles in BUMDes in Tanak Awu Village, Pujut District. This is because the majority of people in Tanaka Awu village are Muslim and there is still a strong sense of mutual cooperation in the community. This study uses a qualitative method. Data obtained through observation, interviews and documentation studies. Furthermore, this data was analyzed by data reduction, data presentation and drawing conclusions. The results of this study are the management and distribution of BUMDes funds in Tanak Awu village based on sharia principles and the results of the analysis of this business concept using SWOT analisis